COMPARATIVE ANALYSIS OF THE RESOURCE ENDOWMENT OF THE ACTIVITY OF XXIIND DIAGNOSTICS AND CONSULTANCY CENTER AND XXIVTH DIAGNOSTICS AND CONSULTANCY CENTER IN SOFIA FOR THE PERIOD FROM THE YEAR 2016 TO 2018 - Desislava Todorova; Tsvetelina Mihaylova; Tsvetomir Dimitrov; Dimitar Gugutkov (Peytchinski Publishing, 2017)
The main aim of the study is monitoring of the condition and developing of the resource opportunities of two diagnostics and consultancy centres (DCC) for the period from the year 2016 to 2018. The main method is comparative analysis of data for two healthcare institutions for specialized pre-hospital medical aid, which serve the population in different districts of Sofia for the period from the year 2016 to 2018. It was found - upon analysis of the personnel potential - that at XXIInd DCC the correlation between doctors/nurses is 1/0.25, which is below the frames of requirements of the modern standards for qualitative healthcare service of patients in that type of health care institutions and makes difficult the work of healthcare professionals. At XXIVth DCC - with a lower number of personnel - there was a higher relative share of administration as compared to XXIInd DCC. The correlation between doctors/nurses at XXIVth DCC was within the frames of requirements, which - along with other parameters - argues for a more effective management of resources and work. The management in both diagnostics and consultancy centres is directed towards administration of personnel, medical and subsidiary activities, ways of providing medical services and prices of provided medical aid.